2016
DOI: 10.1111/ffe.12548
|View full text |Cite
|
Sign up to set email alerts
|

Application of the cohesive zone model for analysing the edge crack propagation of steel sheet in the cold rolling process

Abstract: In the cold rolling process, the expansion and coalescence of micro‐defects can make steel sheet quality descend and create edge crack in the steel sheet. And the edge crack can cause the strip rupture completely. In this research, the cohesive zone model (CZM) was used to analyse the initiation and propagation of edge crack in the cold rolling process with the non‐reversing two‐high mill. A bi‐linear traction–separation law was utilized which is primarily given by the CZM parameters including the cohesive str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The RBF sensory neurons function as signals to receive and transmit, and the RBF associative neurons become empowered neurons after assigning c j to each corresponding input vector. The role of RBF responsive neurons is to accept signals from RBF associated neurons, The output t k of the RBF response neuron r k is a linear combination of output value o j of the RBF association neuron [5].…”
Section: Study On the Mapping Relationship Between Process Parameters And Aluminum Profile Propertiesmentioning
confidence: 99%
“…The RBF sensory neurons function as signals to receive and transmit, and the RBF associative neurons become empowered neurons after assigning c j to each corresponding input vector. The role of RBF responsive neurons is to accept signals from RBF associated neurons, The output t k of the RBF response neuron r k is a linear combination of output value o j of the RBF association neuron [5].…”
Section: Study On the Mapping Relationship Between Process Parameters And Aluminum Profile Propertiesmentioning
confidence: 99%
“…If, however, δ max is larger than δ 2 , then the maximum stress σ max is evaluated in a similar fashion to Equation (15), by using the monotonic damage variable D δ max ð Þ of Equation (13), with δ replaced by δ max . The evaluated values from Equations (25) and (26) are provided to the next loading cycle along with the new value of δ at N + ΔN, with δ determined using Equation (16) and applied in Equation (15).…”
Section: Fast-track Featurementioning
confidence: 99%
“…This permits the modelling of advanced behaviour at the cohesive interface and surroundings taking into consideration such things as friction and plasticity . Loading‐unloading hysteresis models are based on the reduction of the interfacial stiffness captured by a cyclic damage variable that evolves or an internal variable that grows; a review of CZMs for fatigue can be found in references herein . The first successful attempt to use a CZM for the simulation of fatigue crack growth is presented in De‐Andrés et al, which introduces a cyclic damage variable D , whose purpose is to quantify the amount of dissipated energy in the fracture process divided by the critical fracture energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Controlling by experience only is insufficient and does not meet the minimum requirements of strip edge quality, thereby causing the endless emergence of defects, such as buckle edge, burr, and imbalance of cutoff ratio. [5][6][7] Therefore, this situation has become a bottleneck problem in the field of technical research.…”
Section: Introductionmentioning
confidence: 99%